Frequency of paediatric facial trauma in a tertiary care dental hospital - Khan, Muhammad Athar; Ishfaq, Muhammad; Akhtar, Mobeen; Rana, Sadiq Amin Ahmed; Kashif, Muhammad (International Surgery Journal, 2017)
Background: The objective of the study was to determine the frequency of various patterns of pediatric facial trauma in the patients attending a tertiary care hospital. Methods: After written informed consent, 191 cases were taken using non- probability purposive sampling. Demographic profile (age, gender, address) was taken. Diagnoses of the distribution of facial fracture were made with help of history, clinical and radiological examination, plain radiographs, OPG (Orthopantomogram), Occipitomental, PA view of face and CT scan, according to the requirement. Pattern of facial trauma i.e. upper third of face (frontal bone, orbital bone), mid facial bones (Maxilla, Zygomatic, NOE noso-orbito-ethmodial complex), dentoalveolar and mandible was noted on the proforma attached. Data was entered and analysed using SPSS 20.0. Results: The mean age of the patients was 6.50±3.72 years. In this study, 112 (58.63%) were males and 79 (41.37%) were females. So, the male to female ratio were 1.41:1. The mandible was the most commonly fractured bone 58 (30.36%) followed by dentoalveolar, maxilla, zygomatic, NOE complex, orbital and frontal bones fractures. Conclusions: Mandible is the most prone to fracture in paediatric patients.